REKONSTRUKSI PENEGAKAN HUKUM POLITIK UANG DALAM PEMILIHAN KEPALA DAERAH BERBASIS HUKUM PROGRESIF - Imawan Sugiharto (UNISSULA, 2016)
Law enforcement ban on the provision of money or other materials to influence voters in both the legislative elections and the elections of regional heads although in practice the naked eye and is no longer a public secret, but the law enforcement feels very weak. Rarely may not even have happened, law enforcement is applied to Regional Head-Deputy Head candidates who caught giving money or other material known as money politics to win their partner is done transparently, even go to court. In practice, law enforcement is applied only to the person who was caught giving money to someone for choosing a particular candidate. Whereas those arrested is only a messenger of others, for example the Campaign Team of Regional Head Deputy Head Candidates. The purpose of this study was to analyze the influential factors against law enforcement of money politics in regional elections, to find out the shortcomings of political money law enforcement and law enforcement to reconstruct the money politics of the regional elections based progressive law. The results of the research which were done by separating the reconstruction of administrative sanctions such as canceling regional head-deputy head candidates who are convicted of money politics by the Provincial Election Commission or Regional Election Commission upon the recommendation of the Provincial Election Supervisory Board or Regional Election Supervisory Board where the regional head election ongoing and should not wait for the criminal process. While the process of examination of criminal offenses against the political actors of money in provincial or regional elections remain to be done in accordance with the provisions stipulated in the Criminal Procedure Code.